The use of compaction in the manufacture of tablets - O. V. Tryhubchak; Т. А. Groshovyj; O. О. Yuryeva (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
In the production of tablets direct compression method, wet and dry granulationare used. Dry granulation can be used if materials have sufficient cohesive properties to form granules. Scientific publications of recent years clearly demonstrate the prospects of roller compaction using in pharmaceutical industry.